Factors Affecting Financial Statement Fraud in Banking Sector: A Agency Perspective - Fitriana, Larasati; Sinarasri, Andwiani (Universitas Muhammadiyah Semarang, 2024)
This study aims to re-examine the factors that affect financial statement fraud. The population of this study is banking companies listed on the Indonesia Stock Exchange. The sampling technique in this study uses purposive sampling with an analysis unit of 145 financial statements with 29 companies as observations. The results showed that financial targets positively affect financial statement fraud because the higher the financial target, the higher the management acts on financial statement fraud. Financial stability does not affect financial statement fraud because bad financial conditions do not cause management pressure to commit financial statement fraud, which will cause various adverse conditions in the future. External pressure does not affect financial statement fraud because the company can use its debts well to utilize its assets and pay its obligations through the agreement. Independent commissioners do not involve financial statement fraud because they are hired only as a condition of the company so that its governance looks good.